1972
DOI: 10.1126/science.175.4021.538
|View full text |Cite
|
Sign up to set email alerts
|

Prostaglandin E 1 in Preparation and Storage of Platelet Concentrates

Abstract: The addition of prostaglandin E(1) to blood collection bags improved platelet harvesting; platelets were, esily suspended immediately after centrifugation. The treatment with prostaglandin E(1) did not affect the survival time of these platelets after infusion into a recipient.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
3
0

Year Published

1972
1972
2012
2012

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(3 citation statements)
references
References 4 publications
0
3
0
Order By: Relevance
“…Prostaglandin E 1 (PGE 1 ) is a reversible inhibitor of platelet activation because of its ability to increase cyclic AMP levels within the platelets . Although early studies showed that the addition of PGE 1 to human PRP facilitated the separation, concentration, and resuspension of platelets, there have been no studies of the effects of PGE 1 on the preparation of PC in dogs. The aim of this study was to investigate the efficacy of adding PGE 1 during PC preparation.…”
mentioning
confidence: 99%
“…Prostaglandin E 1 (PGE 1 ) is a reversible inhibitor of platelet activation because of its ability to increase cyclic AMP levels within the platelets . Although early studies showed that the addition of PGE 1 to human PRP facilitated the separation, concentration, and resuspension of platelets, there have been no studies of the effects of PGE 1 on the preparation of PC in dogs. The aim of this study was to investigate the efficacy of adding PGE 1 during PC preparation.…”
mentioning
confidence: 99%
“…Because platelet activation is normally inhibited by factors that raise the level of cyclic adenosine 3′, 5′ monophosphate (cAMP), 9–11 attempts have been made, by the addition of cAMP‐activating agents, to improve and extend the storage of PCs for transfusion. These include adenylate cyclase stimulators, such as prostaglandin E 1 or forskolin, and camp phosphodiesterase inhibitors, such as theophylline or isobutyl‐methyl‐xanthine 12–17 . In addition, a solution made up of second‐messenger effectors, named ThromboSol, has recently been reported 18 to limit the known defects induced by refrigerated storage of PCs 19–26 and to lower cytokine accumulation and bacterial growth from that seen with PCs stored at 22°C 27 …”
mentioning
confidence: 99%
“…The present study was undertaken to investigate the benefits of adding prostaglandin El (PGEJ (56 nM final concentration) in vitro during routine PC preparation. Early studies showed that the addition of low concentrations of PGEl to whole blood facilitated the separation, concentration and resuspension of platelets (Becker et al, 1972(Becker et al, , 1974Shio & Ramwell, 1972;Valeri et al, 1972). In addition, Menitove et al (1986) demonstrated that the P-thromboglobulin (P-TG) release and thromboxane B2 (TxB2) production associated with the preparation and storage of PCs was significantly reduced when PGEI was added to PRP prior to centrifugation.…”
mentioning
confidence: 99%